Strong Lp Solutions of Magnetohydrodynamic Equations in R3 - Dr. Jayashree S Gawande, (International Journal of Scientific Research in Science and Technology, 2026)
In this paper we discuss some results on existence and unique solution of local, mild and global solution (u, b) of the three-dimensional Magnetohydrodynamic equations on the space R^3. The MHD equation governing the interaction between the velocity field and the magnetic field is analysed under suitable ini tial data by using various inequalities and L^p-L^qestimates.
Keywords: Magnetohydrodynamics; Strong solutions; L^pspaces; Incompressible flow